Hybrid Fishnet Metamaterial Based on Liquid Crystal and P-I-N Diodes for Reconfigurable Transmitarrays at $10 \,GHz$ - Adrian Diepolder; Lukas Schmidt; Susanne Brandl; Philipp Hinz; Christian Waldschmidt; Christian Damm (IEEE Journal of Microwaves)
This article presents a reconfigurable unit cell for transmitarrays at $10 \,GHz$ based on the fishnet metamaterial structure. The proposed design achieves a phase shift of up to $180 \mathrm{^{° }}$ between different states and additional tunability in each phase state by switching the electric response using p-i-n diodes and simultaneously tuning the magnetic response by employing liquid crystal. Thus, it offers the potential to overcome the limitations of switchable unit cells with few discrete phase states in terms of achievable antenna gain and side lobe level. With an insertion loss of $1.8$ – $2.5 \,dB$ in combination with its high phase tunability it exhibits much higher performance than designs using only liquid crystal. A lumped-element model for prediction of the unit cell behavior is proposed, allowing to reduce the number of full-wave simulations during performance analysis. The biasing network for the liquid crystal is designed for integration in an active-matrix configuration, greatly reducing the complexity of the control circuit. To verify the proposed design, a single unit cell prototype is manufactured and measured inside a waveguide simulator, demonstrating good agreement with full-wave simulations.